Utilization of Health Operational Assistance (BOK) in Nutrition Services in Public Health Center (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Since BOK was launched in 2010, BOK utilization rate continued to increase while the NTT provincial nutrition service coverage did not increase, until 2013. This research aimed to analyze the relationship between the availability of operational funds, the availability of human resources, officer’s knowledge, infrastructure support, heads support and the appropriateness of fund utilization using BOK in nutritional services. This was a quantitative research which supported by a qualitative, cross-sectional design in 2015. The total sample of 250 health workers in 26 health centers of North Central Timor regency was included in this study. Data analysis was done using descriptive, bivariate and multivariate analyses. The results of the bivariate analysis using chi square test showed an association of (p 0.05) the availability of human resources (p = 0.017), officer’s knowledge (p = 0.000), infrastructure support (p = 0.004), heads support (p = 0.000) and the appropriateness of BOK fund utilization (p = 0.000) with the use of BOK in nutritional services. Meanwhile, the availability of operational funds is not associated with the use of BOK in nutritional services. Multivariate analysis showed that health centers with adequate human resources availability are seven times more likely to take advantage and make a good use of the nutritional services using BOK compared to health centers with the lack of human resources, after the infrastructure and head variable controlled. The government is required to provide adequate human resources, including financial administrative personnel and operational funding for health centers to optimize nutritional services. The government also needs to monitor the use of funds regularly and tiered to improve service coverage at the health center.